Monazite EMP age constraints on deformation along ductile shear zones in the Delhi Fold Belt: implications on Neoproterozoic tectonic evolution of NW India - Just, J.; Shulz, B.; de Wall, H.; Jourdan, Fred; Pandit, M. (Elsevier Science BV, 2011)
The in-situ “chemical” Th–U–Pb dating of monazite with the electron microprobe is used to unravel the Neoproterozoic tectono-thermal history of the “Erinpura Granite” terrane in the foreland of the Delhi Fold Belt (DFB) in the NW Indian craton. These granitoids are variably deformed and show effects of shearing activity. Monazites from the Erinpura granitoids recorded two main events; (1) protolith crystallization at 863 ± 23 Ma and (2) recrystallization and formation of new Th-poor monazite at 775 ± 26 Ma during shear overprint. Some components of the Erinpura granitoids, such as the Siyawa Granite and granites exposed near Sirohi town, show evidence of migmatization. This migmatization event is documented by anatexis and associated monazite crystallization at 779 ± 16 Ma. The age data indicate an overlap in timing between anatectic event and ductile shear deformation. The end of the tectono-thermal event in the Sirohi area is constrained by a 736 ± 6 Ma Ar–Ar muscovite age data from the ductile shear zone.